The legitimization strategy of the Taliban's code of conduct: through the one-way mirror - Nagamine, Yoshinobu (Palgrave Macmillan, 2015)
"The Afghan Taliban are often judged against international norms; what is however less known is that they have produced their own set of norms designed to guide their conduct. In this insightful study, Yoshinobu Nagamine examines the Taliban's internal Code of Conduct, the Layeha. Nagamine analyzes the Layeha in comparison with Islamic Law and international humanitarian law and conducts interviews with Taliban members to understand how they interpret and refer to the Layeha. The results of these interviews give readers an insider's view into the legitimization strategy of the Taliban leadership. This work makes a significant contribution to research on non-state actors, counter-insurgency, and Islamic fundamentalism, and it serves as an indispensable resource for scholars of the Afghan Taliban"